In the Tiger's shadow : the autobiography of an Ambedkarite - Nimagaḍe, Ena. Ema (Navayana Pub., 2010)
Autobiography of Nimagaḍe Ena. Ema., b. 1925, agricultural scientist belonging to the Dalit groups of India; translated from Marathi.